2019
DOI: 10.3989/mc.2019.12918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different PVA and steel fiber length and content on mechanical properties of CaCO<sub>3</sub> whisker reinforced cementitious composites

Abstract: In this paper, calcium carbonate (CaCO3) whisker as a fiber reinforcement is mixed with steel and PVA fiber to form a multiscale hybrid fiber reinforced cementitious composites (MHFRCC). ASTM standard and post-crack strength techniques are performed to evaluate the mechanical properties of MHFRCC. The 1.25 % long steel fiber, 0.55 % short PVA fiber and 2.0 % CaCO3 whisker specimens showed the best flexural behavior before L/600 deflection. However, 1.5 % long steel fiber, 0.4 % long PVA fiber and 1.0 % CaCO3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“… Synthetic polymer fibers used in CBMs. ( a ) Polypropylene [ 135 ], ( b ) Polyvinyl alcohol [ 136 ], ( c ) Polyethylene terephthalate [ 137 ], ( d ) Nylon [ 138 ], ( e ) Polyester [ 139 ], ( f ) Aramid [ 140 ]. …”
Section: Figurementioning
confidence: 99%
“… Synthetic polymer fibers used in CBMs. ( a ) Polypropylene [ 135 ], ( b ) Polyvinyl alcohol [ 136 ], ( c ) Polyethylene terephthalate [ 137 ], ( d ) Nylon [ 138 ], ( e ) Polyester [ 139 ], ( f ) Aramid [ 140 ]. …”
Section: Figurementioning
confidence: 99%
“…Plain cement-based composites are known to be brittle material that fails without warning. Due to this brittleness, it has relatively low tensile strength and less resistance against cracking [1]. The crack resistance and tensile strength of cement-based composites are improved with the addition of hybrid fibers [2].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, a micron CaCO 3 whisker (CW) was introduced into a hybrid system of steel fiber and polyvinyl alcohol (PVA) fiber to develop multi-scale fiber reinforced cement matrix composites (MSFRCs). This MSFRC can achieve multi-level and multi-scale strengthening of cement matrix composites and improve the flexural tensile strength, flexural tensile strength, and toughness of cement matrix composites [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Other studies have shown that CW could be mixed with macroscopic fibers to improve composite mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The steel fiber provides the bridging effect in fiber reinforced concrete over a large temperature range and does not melt at temperatures less than 1300 °C [ 9 , 28 , 29 , 30 ]. Previous studies showed that the addition of PVA fiber had considerably enhanced the mechanical properties and toughness of composites and performed as a compatible reinforcing fiber for cementitious composites [ 10 , 12 , 14 ]. In addition, the calcium carbonate whisker (CW) as a micro-fiber performed well at the micro-level and decomposed at 800–900 °C in composites [ 7 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%